2017
DOI: 10.32674/jis.v7i1.249
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Elements of Academic Honesty

Abstract: We examined the impact of a workshop on Asian international graduate students’ understanding of a U. S. American university’s concept of academic honesty. The workshop, taught from a cultural perspective, explained the U.S. American university’s expectations to 19 participants. Data was obtained from a workshop post-test and from subsequent interviews of three workshop participants who relayed their views of textual practices in their home countries. Sixty-seven graduate students from the general graduate stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Moreover, this leads to the following question: What impact does this emergency immersion into online learning by many universities may have on faculty and students' confidence in technology-enabled learning (Lederman, 2020). The above arguments and question have been supported by the results of a study conducted by Thompson et al (2017) which demonstrated that true academic learning and academic honesty are fully achieved through cult-learning in physical face to face classrooms. This current research asked respondents about their final grades as well as their cumulative grade point average (GPA) as a measure for their academic performance.…”
Section: Academic Performance Versus True Academic Learningmentioning
confidence: 89%
“…Moreover, this leads to the following question: What impact does this emergency immersion into online learning by many universities may have on faculty and students' confidence in technology-enabled learning (Lederman, 2020). The above arguments and question have been supported by the results of a study conducted by Thompson et al (2017) which demonstrated that true academic learning and academic honesty are fully achieved through cult-learning in physical face to face classrooms. This current research asked respondents about their final grades as well as their cumulative grade point average (GPA) as a measure for their academic performance.…”
Section: Academic Performance Versus True Academic Learningmentioning
confidence: 89%
“…Teachers should teach international students the concept of ownership of ideas by practically showing the importance of "academic" honesty (Thompson et al, 2017). If a student can't see how "ideas" can be stolen, the first thing a teacher needs to do is to illustrate cases where ideas are people's means of living, their intellectual property and professional achievements.…”
Section: Recommendations For College Teachersmentioning
confidence: 99%
“…Student academic dishonesty also varies by discipline and demographics, and research has shown there is more cheating in professional disciplines such as medicine, business, law and engineering due to competition and peer pressure compared to humanities and social sciences [13]. International students also have unique perspectives on academic dishonesty as norms of intellectual property can vary among cultures and non-native language speakers' way of learning in a new culture and language setting may also lead to students' misunderstanding on academic integrity [14], [15].…”
Section: Introductionmentioning
confidence: 99%